Družbena pogodba - Svete, Sebastjan (Pravnik, 2025)
A social contract comes into being once the existence of a community is no longer the product of a natural urge for self-preservation. It consists of unspoken, yet tacitly accepted and recognised, provisions that enable each individual to be defended and protected by the force of all. The force of all the cocontractors is transformed into a common will, and one of the key issues for society is the recognition - or the management - of this collective force. In this context, in relation to the State and the exercise of public authority, society has evolved from being a mere recipient to becoming a co-creator in that exercise. The prerequisite for successful managing the common force for the benefit of all is a functioning public sphere. Such a sphere requires a clear public interest and a plural society with as many deliberating and participating members as possible. The continual modification or revision of the social contract is in the vital interests of both society and the individual, and is shaped and guided by the functioning public of a democratic society, whose principal purpose is to ensure equal conditions and equal opportunities - within the limits of natural endowments - for every member. The fundamental condition for all this is the active individual.
Keywords: družba; družbena pogodba; force; javnost; justice; pravičnost; public; sila; social contract; society